Influence of anthropogenic activities on marine mammal strandings in the estuary and northwestern Gulf of St. Lawrence, Quebec, Canada, 1994–2008 - Larose-Truchon, Marie-Hélène; Measures, Lena; Brêthes, Jean-Claude; Albert, Elaine; Michaud, Robert (J. Cetacean Res. Manage., 2023)
Stranding records have long been used to monitor marine mammal mortalities and to help identify threats to populations. In coastal areas, marine mammals face numerous anthropogenic threats such as marine traffic and commercial fishing. The objective of this study was to investigate marine mammal stranding records from the St. Lawrence Estuary (SLE) and the northwestern Gulf of St. Lawrence (NWGSL), Quebec, Canada from 1994 to 2008 for evidence of anthropogenic trauma caused by entanglement in fishing gear, ship collisions and gunshots. Of 1,590 marine mammal stranding records, 12% (n = 192) had evidence of anthropogenic trauma, most incidents being reported during summer when activities such as marine traffic, most commercial fishing and recreational boating, occurred and a greater number of species were present in the area. These incidents were classified into five categories (Incidental catch, Ship collision, Severe injury, Gunshot, Other). There were 1,245 mortalities and observations on carcasses suggested that anthropogenic trauma led to the death of 11% (141/1,245) of marine mammals: 14% (87/627) of cetaceans and 9% (54/618) of seals. Mortality of seals due to anthropogenic trauma was low, involving mainly Gunshot for grey (26% or 8/31) and harbour seals (26% or 8/31). Over the study period, marine mammal incidents with evidence of anthropogenic trauma increased significantly, driven by an increase in Incidental catch for two mysticete species, the common minke whale, 42% (39/92) and humpback whale, 13% (12/92) and Other for harbour porpoise 67% (16/24). Ship collision was the most common anthropogenic trauma for fin whales (22% or 8/36) and SLE beluga5 (22% or 8/36). Severe injury was reported for 22% (2/9) of small cetaceans and 78% (7/9) of seals. Evidence from some harbour porpoise stranding records (categorised as Other) suggests illegal hunting, incidental catch, predation or scavenging by grey seals in a marine protected area. The observed increase in Incidental catch of common minke and humpback whales may be due to: (1) a shift in distribution of these two species into the SLE and NWGSL, possibly related to changes in the ecosystem; (2) changes in fishery practices; and (3) an increase in detection of marine mammal strandings. Anthropogenic trauma affecting marine mammals was documented including some species at risk, such as the harbour porpoise, the St. Lawrence Estuary beluga population, blue and North Atlantic right whales, in the St. Lawrence ecosystem including in a marine protected area. This study demonstrates the usefulness of stranding records in helping to monitor human-caused mortality in marine mammal populations.